2018
DOI: 10.1021/acs.jpcc.8b04956
|View full text |Cite
|
Sign up to set email alerts
|

Development of Rh-Doped Ga2O3 Photocatalysts for Reduction of CO2 by H2O as an Electron Donor at a More than 300 nm Wavelength

Abstract: Rhodium-doped gallium oxide (Ga 2 O 3 :Rh) that was prepared by a simple coprecipitation method exhibited activity for the photocatalytic conversion of CO 2 by H 2 O under photoirradiation with light of >300 nm wavelength. Although Ga 2 O 3 is a wide-band-gap photocatalyst that is active only under photoirradiation with <300 nm light, the absorption edge shifted to >300 nm as a result of Rh doping. Ag−Cr-loaded Ga 2 O 3 :Rh (0.7 mol %) showed activity for the production of CO (3.9 μmol h −1 ) as a reduction pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…7(b) shows the relative photocatalytic activities of the b-Ga 2 O 3 nanostructure for different doping materials and concentrations. [16][17][18]26,[57][58][59][60][61] This comparison revealed that the photocatalytic performance of the given Ga 2 O 3 -based photocatalyst increased at certain small amounts of dopants, but decreased with large amounts of dopants. Therefore, an optimal balance between charge separation and recombination via doping approaches is important for Ga 2 O 3 -based photocatalyst.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…7(b) shows the relative photocatalytic activities of the b-Ga 2 O 3 nanostructure for different doping materials and concentrations. [16][17][18]26,[57][58][59][60][61] This comparison revealed that the photocatalytic performance of the given Ga 2 O 3 -based photocatalyst increased at certain small amounts of dopants, but decreased with large amounts of dopants. Therefore, an optimal balance between charge separation and recombination via doping approaches is important for Ga 2 O 3 -based photocatalyst.…”
Section: Resultsmentioning
confidence: 91%
“…26 Cr via Rhodamine B (RhB) degradation under 254 nm, 17 Co via Congo red (CR) degradation under 254 nm, 61 Zn via gas conversion under 254 nm, 18 and Rh via CO 2 conversion under 300 nm. 16…”
Section: Conflicts Of Interestmentioning
confidence: 99%
See 2 more Smart Citations
“…38 Many methods have been investigated to further improve the photocatalytic activity of Ga 2 O 3 , including morphology controlling, doping, surface modication and semiconductor coupling. [39][40][41][42][43][44] Nitu Syed et al reported a two-step method for the synthesis of porous a-Ga 2 O 3 nanosheets from liquid metal gallium, explaining that the excellent photocatalytic activity of a-Ga 2 O 3 originated from the narrowed bandgap caused by trap states. 1 Han et al revealed that the modication of in situ Ag nanoparticles can effectively improve the photocatalytic property of Ga 2 O 3 for hydrogen evolution.…”
Section: Introductionmentioning
confidence: 99%